Teach Intellectual Abilities A Fundamental and Innovative Approach to Teaching Reading - Meeker, Mary. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This paper reports on an innovative approach to the teaching of reading. The thrust of the approach lies in application of findings from Meeker's research which since 1963 had identified certain clusters of Guilford's Structure of Intellect and intellectual abilities found to be necessary in the process of learning to read. Several programs are cited in which teaching the intellectual abilities to children who could not previously read has produced excellent results. The premise that intellectual abilities are prerequisite to learning to read seems well founded, but learning to read does not appear to be a function of a global mental age maturity but depends on various abilities not all of which children have experienced. It is concluded that when the lack of specific intellectual skills is causative in reading failure, then those skills can and should be taught using a method which identifies, diagnoses, and remediates intellectual abilities in children who have not learned to read with traditional methods. (Author/TS)
ERIC Note: Paper presented at the Annual Meeting of the International Reading Association (21st, Anaheim, California, May 1976).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Experimental Teaching; Intelligence; Reading Failure; Reading Instruction; Reading Processes; Reading Programs; Reading Skills; Teaching Methods; Speeches/Meeting Papers